Centralized Monitoring, Resistance, and Reform Outcomes: Evidence from School Inspections in Prussia - Ruth Schueler (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
During the Kulturkampf at the end of the nineteenth century, Prussian authorities introducedcentralized inspections to improve school outcomes in particular in Catholic regions. Tomeasure the effect of the reform, I combine unique data on school inspectors with Prussiancounty-level data. I apply a difference in difference approach exploiting regional differencesin the introduction of the reform. I find positive effects of the reform on school performancein interdenominational regions but no effect in predominantly Catholic regions. An increase inprivate enrollment in the latter regions provides further evidence for Catholic resistance.
Keywords: N33; I21; 330; Prussian economic history; education; monitoring; reform; resistance